Sisters of Prometheus unmasking women's achievements in chemistry - André, João Paulo (Springer, 2024)
Perfumers and Hermetists -- Nuns and Alchemists -- Chastes and Keepers of Secrets -- Atomists and Femmes Savantes -- Illuminated and Revolutionaries -- Authors and Readers.